PENGARUH SIKAP KEWIRAUSAHAAN DAN MOTIVASI TERHADAP MINAT DALAM DUNIA BISNIS - Mahesa, Rangga; Khuluq, Muhammad Husnul; Syaifudin, Arif; Kurniawan, Devi; Sundana, Hari; Rahmawati, Imelda Dian (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the impact of climate change and motivation on the interests in the business world in the student environment of the University of Muhammadiyah Sidoarjo. Using descriptive quantitative methods and associative methods, this study involved 45 respondents who were selected by purposive sampling. Data collected through questionnaires were compiled to measure the level of awareness, motivation, and entrepreneurial behavior. The results of the analysis showed that there is a significant relationship between belief and motivation towards interests in the business world, with a positive value of cooperation. In addition, integrated motivation serves as a mediating variable that strengthens the relationship between desires, expectations and interests. And strong motivation is very important to increase the number of students in entrepreneurship. This research is expected to contribute to the development of entrepreneurship among students and become a hope for educational institutions in designing programs that support the improvement of small businesses. Thus, the results of this study can be the basis for efforts to improve the quality of education in Indonesia